The heart of the Gospel : the theology behind the master plan of evangelism - Coleman, Robert Emerson, 1928- (Grand Rapids, Mich. : Baker Books, 2011)
"For more than forty years, Robert E. Coleman's bestselling The Master Plan of Evangelism has been the standard in evangelism literature. Based on decades of classroom teaching, The Heart of the Gospel offers a systematic theology of evangelism that will ground and inform our practice of spreading the Good News. Each chapter covers a major biblical doctrine, explains its various evangelical interpretations, treats misconceptions that adversely affect evangelism, and offers practical applications of the doctrine. This is the capstone book from a veteran evangelist, teacher, and author" -- BACK COVER.
The character of God -- Revelation and the Bible -- Creation and the celestial hosts -- Creation of man and woman -- Rebellion against God -- The Son of God -- The death of Christ -- The triumph of Christ -- The Holy Spirit -- The grace of God -- Coming to Christ -- The new life -- Sanctification -- Perseverance of the saints -- The church and her ministry -- The return of the King -- The providence of God -- The coming glory.
Includes bibliographical references and index.
Keywords: Evangelistic work -- Philosophy; Theology, Doctrinal